A model for stress‐dependence of apparent permeability in nanopores of shale gas reservoirs. Issue 10 (25th July 2020) - Hatami, Mohammad; Bayless, David; Sarvestani, Alireza
Abstract: Predicting long‐term production from gas shale reservoirs is a challenging task due to changes in effective stress and permeability during gas production. Unlike coal, the variation of sorbing gas permeability with pore pressure in shale does not always feature a biphasic trend under a constant confining pressure. The present contribution demonstrates that the biphasic dependence of permeability on pore pressure depends on a number of physical and geometrical factors, each with a distinct impact on gas permeability. This includes pore size, adsorption isotherm, and the variation of gas viscosity with pore pressure. A single‐capillary model is proposed for the apparent permeability of real gas in shale. Results indicate that the biphasic relation between apparent permeability and pore pressure is prevalent when the sorbing gas flows in sufficiently small pores. In addition, the effects of sorption isotherm and internal resistance of nonideal gas to flow cannot be ignored.